Step
*
1
1
of Lemma
Wadd-assoc
1. A : Type
2. B : A ⟶ Type
3. zero : A ⟶ 𝔹
4. a : A
5. ¬↑(zero a)
6. ¬False
7. f : B[a] ⟶ W(A;a.B[a])
8. ∀b:B[a]. ∀w2,w1:W(A;a.B[a]).  ((w1 + (w2 + f b)) = ((w1 + w2) + f b) ∈ W(A;a.B[a]))
9. w2 : W(A;a.B[a])
10. w1 : W(A;a.B[a])
⊢ Wsup(a;λx.(w1 + (w2 + f x))) = Wsup(a;λx.((w1 + w2) + f x)) ∈ W(A;a.B[a])
BY
{ RepeatFor 2 ((EqCD THEN Auto)) }
Latex:
Latex:
1.  A  :  Type
2.  B  :  A  {}\mrightarrow{}  Type
3.  zero  :  A  {}\mrightarrow{}  \mBbbB{}
4.  a  :  A
5.  \mneg{}\muparrow{}(zero  a)
6.  \mneg{}False
7.  f  :  B[a]  {}\mrightarrow{}  W(A;a.B[a])
8.  \mforall{}b:B[a].  \mforall{}w2,w1:W(A;a.B[a]).    ((w1  +  (w2  +  f  b))  =  ((w1  +  w2)  +  f  b))
9.  w2  :  W(A;a.B[a])
10.  w1  :  W(A;a.B[a])
\mvdash{}  Wsup(a;\mlambda{}x.(w1  +  (w2  +  f  x)))  =  Wsup(a;\mlambda{}x.((w1  +  w2)  +  f  x))
By
Latex:
RepeatFor  2  ((EqCD  THEN  Auto))
Home
Index